PHYSIOLOGICAL JAUNDICE OF FIRST BREAST MILK (COLOSTRUM) IN HOSPITAL AIRLANGGA UNIVERSITY - Vista Claudia Sari; Irwanto Irwanto; Widati Fatmaningrum; Martono Martono (Indonesian Midwifery and Health Sciences Journal, 2020)
ABSTRACTBackground: 60-70% of newborns have jaundice and can potentially become pathological jaundice. The effects of jaundice are often incurable, can cause disability to mental retardation. Jaundice is one of the causes of neonatal death. Jaundice accounts for 6% of neonatal deaths. Breastfeeding especially colostrum is often associated as one of the factors that can influence the occurrence of jaundice in newborns. Method: This type of research is descriptive quantitative. The population is all newborns at Airlangga University Hospital, Surabaya. The study was conducted from October to November 2019. Non-random sampling technique with total sampling. Results: There were 159 newborns in RSUA from October to November 2019. 14 newborns were not found in medical records, 10 were not given the first breast milk. Of the 135 research samples given the first ASI 18 samples or 13.33% who experienced physiological jaundice. 94.44% of the total sample of 18 who experienced physiological jaundice were babies born to mothers aged 21-35 years. 66.67% of babies with jaundice are infants with mothers as housewives. 61.11% of babies with high school graduation, 72.22% were born by cesarean section, 72.22% were born with a history of clear membranes, and 61.11% were born by primiparous mothers. Conclusion: Newborns were given first breast milk (Colostrum), 85.2% did not experience jaundice, 13.3% experienced physiological jaundice and 1.5% pathological jaundice. Jaundice can occur due to many factors; maternal, neonatal and perinatal factors.